Recognition factors of Dolichos biflorus agglutinin (DBA) and their accommodation sites - Wu, Albert M.; Dudek, Anna; Chen, Yung Liang (Glycoconjugate journal, 2023)
Dolichos biflorus agglutinin (DBA) is one of the well known plant lectins that are widely used in clinical serology to differentiate human blood group A 1 and A 2 erythrocytes and also applied to glycobiology. However, the knowledge of recognition factors of polyvalent (super) glycotopes in glycans and the roles of functional group and epimer in monosaccharide (sub-monosaccharide recognition factor) have not been well established. The size and shape of the recognition (combining) site of DBA has not been clearly defined. In this study, many important recognition factors of DBA-glycan binding were characterized by our established enzyme-linked lectinosorbent (ELLSA) and inhibition assays. The results of these assays showed that the intensity profile of the recognition factors for the major combining site of DBA was expressed by Mass relative potency (Mass R.P.) and shown by decreasing order of high density of polyvalent GalNAcα1 → (super glycotopes, 3.7 × 10 3 ) >> the corresponding β anomers >> monomeric GalNAcα1 → related glycotopes (GalNAc as 1.0) >> their GalNAc β-anomers >> Gal (absence of NHCH 3 CO at carbon-2 of GalNAc) and GlcNAc (different epimer of Carbon-4 in GalNAc). From the all data available, it is proposed that the combining site of DBA should consist of a small cavity shape as major site and most complementary to monomeric GalNAcα → located at both terminal reducing end (Tn) and nonreducing end of glycan chains, and with a wide and broad area as subsite to accommodate from mono- to tetra-saccharides (GalNAcβ, Galβ1 → 3/4GlcNAc, l Fucα1 → 2Galβ1 → 3/4GlcNAc, GalNAcβ1 → 3Galα1 → 4Galβ1 → 4Glc) at the nonreducing side. This study provides the most (comprehensive) recognition knowledge of DBA-glycan interactions at the factors of glycotope, super glycotope/sub-monosaccharide levels. Thus, it should expand and upgrade the conventional concept of the combining (recognition) site of DBA since 1980s.